Adhesion and proliferation behavior of primary human mesenchymal stem cells on sulfated cellulose nanofiber scaffolds with different sulfate contents - Ritomo Kai; Mayumi Hatakeyama; Shinichiro Iwamoto; Takuya Kitaoka (Carbohydrate Polymer Technologies and Applications, 2025)
Primary human mesenchymal stem cells (hMSCs) have attracted much attention in regenerative medicine, where stem cell culture currently requires xeno-free (xenogeneic component-free) systems for both media and scaffolds. Herein, we propose plant-derived, sulfated cellulose nanofibers (S-CNFs) with different sulfate contents as a novel xeno-free scaffold. Primary and immortalized hMSCs were cultured on S-CNF scaffolds with different sulfate contents (0–1.69 mmol g–1) under serum-free conditions. The cell proliferation behavior was sensitive to the sulfate content, although the original CNFs did not contribute to cell adhesion. In particular, S-CNF scaffolds with sulfate contents of 0.31–0.47 mmol g–1 demonstrated more efficient cell growth than a standard polystyrene substrate and comparable cell growth to animal-derived type I collagen. The engineered S-CNF scaffolds with the optimal sulfate content promoted the initial cell adhesion and proliferation of primary hMSCs by facilitating the formation of focal adhesions. In addition, these scaffolds improved the stability and efficacy of growth factors in serum-free environments, potentially contributing to their functional preservation in xeno-free culture systems. Our strategy of using S-CNFs as a new medical modality provides new insights into the development of xeno-free culture systems in cell culture engineering.